Pension-related application of the cohort life table - Gogola, Ján; Slavíček, Ondřej (Masarykova univerzita, 2016)
Longevity risk, the risk that people will live longer than expected, weighs heavily on those who run pension schemes and on insurers that provide annuities. Hence the prediction of future mortality rates is an issue of fundamental importance for the insurance and pensions industry. Our analysis focuses on mortality at higher ages (65-95), given our interest in pension-related applications where the risk associated with longer-term cash flow is primarily linked to uncertainty in future rates of mortality. The Lee-Carter model became one of the most applied models and it is used to forecast age-specific death rates. The main goal of this paper is to apply the Lee-Carter model to construct the so-called “cohort life tables” for calculation of a 30-year annuity to a person aged 65 in 2015. We use data on deaths and exposures for the Czech Republic from the Human Mortality Database (HMD). The HMD provides evidence that life expectancy is increasing. We have shown that if the today rate of increase will continue, it will at age 65 concluded (after calculation) to increase the present value of pension liabilities in defined-benefit schemes about 5 % if we use cohort life table instead of period life table. Probability statements derived from the use of a single model and parameter set should be treated with caution. Hence, there is a need for awareness of model risk when assessing longevity-related liabilities.
Aplikace kohortních úmrtnostních tabulek pro výpočet penze.
Keywords: longevity risk, annuity, stochastic mortality, life table, Lee-Carter model; riziko dlouhověkosti, anuita, stochastický model úmrtnosti, úmrtnostní tabulky, Lee-Carter model